Evaluation of bee wax propolis inhibitor for corrosion protection on stainless steel in various pH solution. (December 2022) - Gapsari, Femiana; Wijaya, Hastono; Septiari, Renny; Andoko,
Abstract: The protective ability of an organic inhibitor varies and is affected by the pH of the solution. Related with this fact, this work investigated corrosion inhibition performance of Bee Wax Propolis (BWP) extract on 304 SS in various environment (0–14 pH). The BWP extract inhibitor had formed a passive layer on the surface, indicated by the increase of the passive region. The inhibition efficiency changed randomly at all pH. The optimum inhibition efficiency for the acid and alkaline condition happened at pH 2 (96.60%) and 12 (97.75%). BWP was found to control corrosion better at pH 2 and 12.